Policy entrepreneurs and collaborative action: pursuit of the sustainable development goals. (2018) - Mintrom, Michael; Thomas, Madeline
Entrepreneurs use their access to information and strategic savvy to develop and bring new products and services to market. Often, their actions catalyse whole new forms of economic and social activity. Such entrepreneurship is not restricted to the marketplace. Over recent decades, social scientists have studied the practices of actors in and around government who have been described, among other things, as policy entrepreneurs or institutional entrepreneurs. Attention has also been given to social entrepreneurs, who use knowledge of business practices to advance solutions to major social problems. We consider here how policy entrepreneurs engage in collaborative action to promote broad societal changes, focusing on pursuit of the United Nations' sustainable development goals (SDGs). We review entrepreneurial action across institutional settings. We then discuss how policy entrepreneurs can catalyse change processes to achieve the SDGs. After presenting an illustrative case, we propose directions for future research.